Anti-Aging and Antioxidant Activities of Clitoria ternatea L. Flower Extract - Lucianus, Johan; Adhika, Oeij Anindita (Bogor Agricultural University, Indonesia, 2026)
Aging is influenced by several factors, including Reactive Oxygen Species (ROS). An imbalance of higher ROS and lower antioxidants may lead to oxidative stress in cells that is manifested as wrinkles, dark spots, and fine lines. Antioxidants can prevent the effects of ROS. Safe and abundant sources of antioxidants can come from natural ingredients. One of the natural ingredients widely studied is Clitoria ternatea flower extract (CFE). This study aims to report the CFE potential as an anti-aging and antioxidant agent. Gallic acid and quercetin standards were used to measure the total flavonoid and phenolic content. Antioxidant activity was evaluated by hydroxyl (OH) and Nitric Oxide (NO) scavenging, while anti-aging activity was evaluated by collagenase and elastase inhibition tests. CFE showed high phenol and flavonoid content (14.49 μg GAE/mg and 9.00 μg QE/mg). CFE also has OH and NO scavenging activity with IC50 18.39 and 31.11 μg/mL, which exhibited antioxidant potential. CFE also showed potential to inhibit collagenase (IC50 = 177.48 μg/mL) and inhibit elastase (IC50 = 30.88 μg/mL). CFE may serve as a promising candidate with antioxidant and anti-aging properties.